Cardiovascular events as the effect of targeted therapy - Szmit, Sebastian; Opolski, Grzegorz; Szczylik, Cezary (Contemporary Oncology/Współczesna Onkologia, 2008)
The introduction of targeted therapies has been a breakthrough in present day oncology. These medicaments have proved their high clinical effectiveness. By working in specific mechanisms and on exactly determined metabolic points, these medicines should have an insignificant percentage of complications. There is a paradox, that they block the cell\'s metabolism, which is very important for cardiomyocytes. The small molecule tyrosine kinase inhibitors, while blocking the pathways of neoangiogenesis in the neoplasm, also raise the risk of cardiotoxicity. They also contribute to the occurrence of myocardial dysfunction and hypertension. These medicaments cause acute coronary syndromes and thromboembolic events. Anti-HER2 therapy is also cardiotoxic. It blocks the receptor which normally protects the heart from impairment factors (ischaemia, toxins, adrenergic stimu-lation). Cardiovascular events related to targeted therapy are very often asymptomatic, without the indicators of myocardial necrosis. This cardiotoxicity is often dependent on usage of other cytostatics (mainly anthracyclines). The response to typical cardiological treatment is very good, and healing is achieved very quickly. The oncological benefit is significantly higher than the potential cardiovascular risk.